2007
DOI: 10.1016/j.adolescence.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal substance use and HIV status: Adolescent risk and resilience

Abstract: We examined the risk and protective factors and mental health problems of 105 low SES, urban adolescents whose mothers were coping with alcohol abuse and other drug problems. Approximately half of the mothers were also HIV-infected. As hypothesized, there were few differences between adolescents of HIV-infected and HIV-uninfected mothers in background characteristics, mental health issues and current substance use risk behaviors. In addition to maternal substance abuse, youth in both groups experienced similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 66 publications
1
18
3
1
Order By: Relevance
“…Studies examining the relationship between caregiver HIV status and HIV-negative youth’s’ sexual risk behaviors have found caregiver’s positive status was associated with earlier first sex and greater likelihood of sexual risk behavior in youth (Lee, Lester & Rotheram-Borus, 2002; May, Lester, Ilardi, & Rotheram-Borus, 2006; Rotheram-Borus, Draimin, Reid & Murphy, 1997). Conversely, other studies have found no differences or lower rates of sexual (risk) behavior among uninfected youth with HIV+ mothers compared to youth with HIV-mothers (Mellins, Brackis-Cott, Dolezal, & Meyer-Bahlburg, 2005; Mellins, Dolezal, Brackis-Cott, Nicholson, Warne, & Meyer-Bahlburg, 2007; Leonard, Gwadz, Cleland, Vekaria & Ferns, 2008; Murphy, Herbeck, Marelich, & Schuster, 2010). To our knowledge, however, no study has examined prospectively how youth’ sexual development is contextualized by their own and their caregivers’ HIV infection .…”
Section: Introductionmentioning
confidence: 84%
“…Studies examining the relationship between caregiver HIV status and HIV-negative youth’s’ sexual risk behaviors have found caregiver’s positive status was associated with earlier first sex and greater likelihood of sexual risk behavior in youth (Lee, Lester & Rotheram-Borus, 2002; May, Lester, Ilardi, & Rotheram-Borus, 2006; Rotheram-Borus, Draimin, Reid & Murphy, 1997). Conversely, other studies have found no differences or lower rates of sexual (risk) behavior among uninfected youth with HIV+ mothers compared to youth with HIV-mothers (Mellins, Brackis-Cott, Dolezal, & Meyer-Bahlburg, 2005; Mellins, Dolezal, Brackis-Cott, Nicholson, Warne, & Meyer-Bahlburg, 2007; Leonard, Gwadz, Cleland, Vekaria & Ferns, 2008; Murphy, Herbeck, Marelich, & Schuster, 2010). To our knowledge, however, no study has examined prospectively how youth’ sexual development is contextualized by their own and their caregivers’ HIV infection .…”
Section: Introductionmentioning
confidence: 84%
“…In a study of 105 adolescents whose mothers were coping with substance problems, Leonard et al (2008) concluded that despite the numerous risk factors experienced by many paricipants, they exhibited significant signs of resilience. As the ecological theory states, risk factors do not necessarily lead to a predetermined result.…”
Section: The Subjectivity Of Risk and Resiliencementioning
confidence: 97%
“…In particular, a history of crime and especially of substance dependence in the family is considered to be a strong risk factor in itself and also in association with other visible risk factors (Biederman, Faraone, Mounteaux, & Feighner, 2000). When a substance-dependent parent engages in intensive use of drugs, adolescents often experience neglect as they are pushed aside and become secondary to the parent's needs (Barnard & McKeganey, 2004;Leonard, Gwadz, Cleland, Vekaria, & Ferns, 2008). This neglect may be physical, reflected in hygiene, nutrition, and clothing, as well as emotional (Yates & Wekerle, 2009), associated with the parent's distress, depression, low self-esteem, poverty, and violence (Nair et al, 1997).…”
Section: Substance Dependence In the Family As A Critical Riskmentioning
confidence: 99%
“…Domestic violence with physical punishment experience (23)(24)31,56) Difficulties with family relationships (parents and siblings) (13,31,61) Parents and friends influence to use drugs (14,56) Low emotional support at home during childhood (15,60) Alcohol abusive parents (47,54) Parents divorce 0, 19)to de tristeza; átricos. (19) Family financial problems (38) Parents with low well-being levels (52) Bad experience of family communication (52) Parents that live with or died of HIV/Aids (60) 26.4…”
Section: Family Relatedmentioning
confidence: 99%
“…Suffered aggression and physical violence (13,23,29,36,41,48,58) Sexual abuse experience evolving life threatening and physical injuries (13,22,41,43,51,53) Gangs involvement (20,61) Social contact problems and rules violation (25,59) Legal problems, involvement with auto accidents and violent acts practice (59,61) To be not working or studying (12) High frequency of exposition to community violence, theft, assault and firearms use (13) To be institutionalized or living in a shelter (13) Urban poverty (47) 32.0 …”
Section: Socialmentioning
confidence: 99%